Logistics-related determinants of regional gross domestic product - an exploratory investigation - Winter, Matthias; Manuj, Ila; Gerschberger, Markus (European Journal of Transport and Infrastructure Research, 2022)
Existing research suggests a link between a country’s infrastructure quality and its economic performance. However, no country can invest in all types of infrastructure across the country. Therefore, it is critical to identify and assess multiple indicators of infrastructure for regions within a country and focus on improving infrastructure as identified by the weak indicators. Research investigating the determinants of regional wealth and economic growth is limited. In this comprehensive research including all 35 regions in Austria, we began by evaluating the relationship between logistics-related infrastructure and regional gross domestic product. In the process, other indicators, and mediators such as knowledge infrastructure, business attractiveness emerged as impacting gross domestic product. The findings help to better understand the relative importance of diverse logistics indicators influencing regional economic development and provide insights for policy decision-making.